How agritourism helped farmers during the pandemic - Rachael Callahan (California Agriculture, 2023)
During COVID-19, California small farmers and ranchers suffered significant disruptions and shifts in the marketplace, marked by a loss in wholesale outlets and an increase in demand for direct-to-consumer sales. This study examines how agritourism operators responded to the challenges and opportunities created by the pandemic. In 2021 and 2022, in the midst of the pandemic, the UC ANR Agritourism Program held a series of trainings for California farmers interested in starting or expanding agritourism enterprises. Some of the key themes that emerged from the trainings were that farmers had to shift their operations to ensure social distancing and reduced crowd sizes, while at the same time, they experienced an unprecedented demand for direct-to-consumer sales and on-farm visits. Agritourism, in varying degrees, contributed to the resiliency of most of the participants in our study. Moving forward, it would be worthwhile for researchers, agricultural professionals, and decision-makers to examine equity in agritourism and agritourism's role as a risk-management strategy to help mitigate other types of disruptions in the future. Our findings also point to the need to provide farmers with technical assistance around e-commerce and sustainable business planning.